Fathers’ involvement in children’s personal care activities - Baxter, Jennifer; Baxter, J.A. (Australian Institute of Family Studies, 2012)
The roles that fathers play in Australian families are multifaceted, with many fathers being the main income earners, but also being involved in the day-to-day activities of raising children (Baxter & Smart, 2010). While, on average, fathers spend less time than mothers with children and are less involved in tasks associated with the care of children, they nevertheless often have some level of engagement in these activities. This chapter uses data from Growing Up in Australia: The Longitudinal Study of Australian Children (LSAC) to take a closer look at the degree to which fathers are involved with their children's personal care activities and provide insights into this aspect of father involvement.
The Longitudinal Study of Australian Children Annual statistical report 2011
Keywords: Families -- Fathers; Child Care; Families and relationships; Child Care; Families; Fathers; Families and relationships